2011
DOI: 10.1002/cncr.26425
|View full text |Cite
|
Sign up to set email alerts
|

A combined molecular‐pathologic score improves risk stratification of thyroid papillary microcarcinoma

Abstract: Background Thyroid papillary microcarcinoma (TPMC) is an incidentally discovered papillary carcinoma that is ≤ 1.0 cm in size. Most TPMCs are indolent, whereas some behave aggressively. The aim of the study was to evaluate whether the combination of BRAF mutation and specific histopathological features allows risk stratification of TPMC. Methods A group of aggressive TPMC was selected based on the presence of lymph node metastasis or tumor recurrence. A group of non-aggressive tumors included TPMCs matched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
109
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 34 publications
8
109
3
3
Order By: Relevance
“…28,29 The subcapsular/superficial location of papillary thyroid microcarcinoma is believed to be a significant risk factor for aggressive behavior. 30 Therefore, we studied them separately from the classic and the intraparenchymal occult sclerosing types of microcarcinomas but found no significant difference in the prevalence of BRAF V600E mutation. The small size of papillary thyroid microcarcinomas makes histologic subtyping difficult or unclassifiable, and possibly poorly reproducible among pathologists.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…28,29 The subcapsular/superficial location of papillary thyroid microcarcinoma is believed to be a significant risk factor for aggressive behavior. 30 Therefore, we studied them separately from the classic and the intraparenchymal occult sclerosing types of microcarcinomas but found no significant difference in the prevalence of BRAF V600E mutation. The small size of papillary thyroid microcarcinomas makes histologic subtyping difficult or unclassifiable, and possibly poorly reproducible among pathologists.…”
Section: Discussionmentioning
confidence: 92%
“…Despite this limitation, we show that BRAF V600E -mutated papillary thyroid microcarcinomas demonstrate aggressive features at presentation. Niemeier et al 30 have suggested a combined molecular-pathologic scoring system for risk stratification of papillary thyroid microcarcinoma that included: BRAF V600E mutation, superficial location, fibrosis, and multifocality/intraglandular tumor spread but their study too was limited by the absence of follow-up. We found the first three features to be generally present together in mutated microcarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the new era of 2015 ATA guidelines, which adopted the wait and see strategy in low-risk PTC, there still pertain a dilemma of how aggressively low-risk patients need to be treated. Although BRAF mutation is not a prognostic factor for recurrence after initial appropriate treatment, BRAF mutation may be used for a preoperative modulator for the determination of early surgical intervention because of its relationship between BRAF mutation and aggressive tumor behavior as shown in a number of previous studies (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this mutation may help surgeons to determine the extent of thyroid surgery especially in the prophylactic central LN dissection (23). However, other oncogenic mutations will be evaluated in order to identify more specific markers of less favorable PTC outcome in the future, because the BRAF mutation had a low positive predictive value and about 50% patients with BRAF mutation had no LN metastasis (20)(21)(22). The limitations of this study are the short follow-up time and the sensitivity and specificity were not as good as direct DNA sequencing analysis even though the PCRrestriction fragment length polymorphism (RFLP) was a useful method for BRAF mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The group of Nikiforov et al [11] proposed risk stratification of patients with PTMC based upon their BRAF status , and several studies [12,13], but not all [14,15] associate the presence of BRAF with more aggressive biological behavior. Clearly, all PTMC's will not exhibit the same behavior, and we are likely to have only ''scratched the surface'' in the discovery and understanding of other genomic mutations that impact biological behavior and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%